Students’ Mastery in Phrasal Verbs at Fifth Semester Students of English Department in The University of Mataram - Juniartawan, I Putu Adi; Sujana, I Made; Lail, Husnul (Jurnal Ilmiah Pendidikan Indonesia, 2020)
Understanding phrasal verbs is one of the serious problems in learning English for foreign learners of English. This present research aimed to measure the mastery of phrasal verbs and elaborate the problems in using phrasal verbs by students of English Department in the University of Mataram. This study employs case study involving 40 students of English Education Department, the University of Mataram. The data were collected using a test of phrasal verbs in three categories (transparent, semi-transparent, and idiomatic) and questionnaire used to investigate problems. The collected data were then analyzed qualitatively. The result showed that that 65% students below the minimum score of 56 in the test and the result from the questionnaire showed that most students agreed lack of learning, regularity of exposure and mental barriers are their main problems.